2023
DOI: 10.3389/fonc.2023.1153131
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide/platinum plus anlotinib for patients with transformed small-cell lung cancer from EGFR-mutant lung adenocarcinoma after EGFR-TKI resistance: a retrospective and observational study

Abstract: ObjectiveThe histological conversion of lung adenocarcinoma (LUAD) into small-cell lung cancer (SCLC) is an important resistance mechanism for epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI)-resistant LUAD. Anlotinib has been recommended as the third-line treatment for SCLC patients. The efficacy of etoposide/platinum (EP) as the main treatment is very limited for patients with transformed SCLC. However, little is known about EP plus anlotinib for transformed SCLC. The present study ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Furthermore, the ACTION-2 study prospectively reported that the first-line treatment with EP plus anlotinib for extensive-stage de novo SCLC achieved an overall response rate (ORR) of 87.2%, a disease control rate (DCR) of 97.7%, an mPFS of 9.0 months, and an mOS of 19.0 months (39). In our retrospective study, transformed SCLC after EGFR-TKI failure was treated with EP plus anlotinib, reaching 9.0 months of mPFS and 14.0 months of mOS (40). At present, there are no reports about anlotinib treatment for the transformed SCLC from NSCLC on immunotherapy.…”
Section: Therapeutic Strategies For Sclc Transformed From Nsclc After...mentioning
confidence: 86%
“…Furthermore, the ACTION-2 study prospectively reported that the first-line treatment with EP plus anlotinib for extensive-stage de novo SCLC achieved an overall response rate (ORR) of 87.2%, a disease control rate (DCR) of 97.7%, an mPFS of 9.0 months, and an mOS of 19.0 months (39). In our retrospective study, transformed SCLC after EGFR-TKI failure was treated with EP plus anlotinib, reaching 9.0 months of mPFS and 14.0 months of mOS (40). At present, there are no reports about anlotinib treatment for the transformed SCLC from NSCLC on immunotherapy.…”
Section: Therapeutic Strategies For Sclc Transformed From Nsclc After...mentioning
confidence: 86%